HUBUNGAN AGAMA-NEGARA PASCA REFORMASI - Karim, M. Abdul (Islamic University of Indonesia, 2005)
Studying relations between the Religion (Islam) and the state in Indonesia always presented special characteristics. The Islam Religion has become deeply rooted in the Indonesian Moslemâs inner self. The matter is how the state puts Islam in the dynamics of her government form. Until now, we have found Islam can afford to be soul and spirit for implementing changes toward the better ones. Islam spirit has been proved in the historical path of Indonesian nation that it was able to liberate herself from colonial domination, backwardness, and underdevelopment. Thus, in the relations between Islam as a religion institution and the state (government) as a constitutional policy holder donât to suspect each other, but they must be able to result in a new cosmos that is mutually profitable.They are no longer to exploit mutually, but to create harmonization for the sustained nation. Kata kunci: agama, negara, dan reformasi.